Good governance in Bangladesh: Present situation and future challenges - Momen Nurul; Begum Marzina (Međunarodni Problemi)
In this article the authors focus on challenges, experiences and strategies for good governance in Bangladesh. They explore what capacities states need to develop in order to meet the demands and how to strengthen governance institutions, including electoral management bodies, parliaments and judicial systems in Bangladesh.